Chapter 12. Parasitoses in brackishwater aquaculture. - Raja, R.A. (In: Alavandi, S.V., Saraswathy, R., Muralidhar, M., Vijayan, K.K. (Eds.), Perspectives on Brackishwater Aquaculture in India, Aquatic Animal Health and Environment Management, ICAR-Central Institute of Brackishwater Aquaculture (CIBA) & Society of Coastal Aquaculture and Fisheries (SCAFi), Chennai, India,, 2021)
The rapid increase in aquaculture activities raises the quantum of disease incidences globally. The diseases caused by infectious agents are considered to be most significant as many of them do not cause acute disease but lead to chronic disease and cause persistent economic loss to aquaculture. Parasites are one of the major infectious disease agents that cause economic loss to aquaculture. Hence it is necessary to understand the major parasitic prevalence, their identification, and prevention and control measures. Keywords Acanthocephalan, Amoebozoa, Annelids, Apicomplexa, Aquaculture, Argulids, Arthropods, Caligids, Cestodes, Ciliates, Crab, Cymothoids, Digeneans, Dinoflagellates, Ergasilids, Finfish, Flagellates, Gill flukes, Gregarina, Haplosporida, Helminthiases, Lamproglena, Lernaea, Lernanthropids, Linguatula, Metazoa, Microsporidia, Milkfish, Monogeneans, Myxozoa, Nematodes, Pearlspot, Protozoa, Seabass, Shrimp, Skin flukes, Trematodes